2012
DOI: 10.1002/jcb.24376
|View full text |Cite
|
Sign up to set email alerts
|

Secreted phosphoprotein‐24 kDa (Spp24) attenuates BMP‐2‐stimulated Smad 1/5 phosphorylation and alkaline phosphatase induction and was purified in a protective complex with alpha2‐Macroglobulins From Serum

Abstract: Secreted phosphoprotein-24 kDa (Spp24) binds cytokines of the bone morphogenetic protein/transforming growth factor-β (BMP/TGFβ) superfamily and is one of the most abundant serum phosphoproteins synthesized by the liver. Little is known about how Spp24 binding affects BMP signal transduction and osteoblastic differentiation or how this labile protein is transported from the liver to remote tissues, such as bone. When Spp24 was administered to W-20-17 mesenchymal stem cells with rhBMP-2, short-term Smad1/5 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 46 publications
6
25
0
Order By: Relevance
“…This domain also binds transforming growth factor-␤ (TGF-␤) resulting in increased apoptosis (55). SPP24 has also been observed by us and others (65) to exist in a high mass complex bound to ␣-2-macroglobulin and other proteins in serum (supplemental Table S3). SPP24 is present in smooth muscle, epithelial cells and is released from macrophages and T-cells in response to heightened levels of TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…This domain also binds transforming growth factor-␤ (TGF-␤) resulting in increased apoptosis (55). SPP24 has also been observed by us and others (65) to exist in a high mass complex bound to ␣-2-macroglobulin and other proteins in serum (supplemental Table S3). SPP24 is present in smooth muscle, epithelial cells and is released from macrophages and T-cells in response to heightened levels of TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of experimental arthritis increases the expression of Spp24 in joint cartilage by more than 30‐fold, an increase that is greater than that of any other protein [Meng et al, ]. We reported that Spp24 is present in serum in a high molecular weight (>500 kDa) disulfide‐bonded complex with A2Ms (A2M itself, PZP, and C3) and A1AT [Zhao et al, ]. In studies aimed at characterizing the SF proteome of patients with RA and OA, Spp24 was found to be present if A2M, its abundant carrier protein, had not first been depleted to enhance the detection of less abundant proteins [Balakrishnan et al, ].…”
mentioning
confidence: 97%
“…A small fraction of these proteins (∼10–20% in most cases) can also be detected in the basolateral side (bottom well). In addition, all plasma proteins in the secretion media resembled that of A2M/C3 (360–720 kDa, Zhao et al, []) in spite of their differing molecular weights. These results suggested that all the proteins tested exist as a high molecular weight form, most likely with C3 which serves as an intracellular and extracellular chaperone as A2M also seen in synoviocytes [Zhao et al, ].…”
Section: Resultsmentioning
confidence: 99%